2012
DOI: 10.5012/bkcs.2012.33.10.3355
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic Efficiencies on Dye-Sensitized Solar Cells Assembled with Graphene-Linked TiO2Anode Films

Abstract: To promote the photoelectric conversion efficiency of dye-sensitized solar cells (DSSCs), graphene is introduced as a working electrode with TiO 2 in this study, because it has great transparency and very good conductivity. XRD patterns indicate the presence of graphene and TiO 2 particles in graphene-linked TiO 2 samples. Moreover, TEM pictures also show that the nano-sized TiO 2 particles are highly dispersed and welllinked onto the thin layered graphene. On the basis of the UV-visible spectra, the band gaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…These previous reports suggest that the DSSC performance of TiO 2 can be improved with the addition of graphene. Based on the different TiO 2 /graphene photoanode fabrication methods, such as squeeze printing technique , electrodepositing , doctor blade method and heterogeneous coagulation method , the DSSC efficiency also varied. In our present work, rGO–TiO 2 was prepared by rapid thermal reduction method and used as photoanode, and it showed the conversion efficiency of 4.74%.…”
Section: Resultsmentioning
confidence: 99%
“…These previous reports suggest that the DSSC performance of TiO 2 can be improved with the addition of graphene. Based on the different TiO 2 /graphene photoanode fabrication methods, such as squeeze printing technique , electrodepositing , doctor blade method and heterogeneous coagulation method , the DSSC efficiency also varied. In our present work, rGO–TiO 2 was prepared by rapid thermal reduction method and used as photoanode, and it showed the conversion efficiency of 4.74%.…”
Section: Resultsmentioning
confidence: 99%
“…The determination of optical band gap was obtained from the interception of the abscissa axis with the straight line of the ( ℎ ) 1 pure TiO2 because less than 1 wt % of graphene is used. Based on previous report, the amount of graphene used was more than 1 wt % which are 1, 5 and 10 wt % Graphene-TiO2 and give lower band gap value of 2.94, 2.25 and 2.11 eV respectively [18].…”
Section: Optical Band Gapmentioning
confidence: 98%
“…Lately, graphene, the two-dimensional carbon nanomaterial, has gained lots of attention due to its newly discovered amazing and unique characteristics [18,19], such as light weight, high electrical conductivity, large surface area, excellent mechanical strength, and three-dimensional flexibility [20,21]. Many studies [20][21][22][23] showed that CNTs can significantly improve the short circuit current density (J sc ) and power conversion efficiency (η) of dye-sensitized solar cells (DSSCs).…”
Section: -Introductionmentioning
confidence: 99%